Nitrate-Mediated Corrosion Control in Microbial Biofilms: A Sustainable Approach (International Journal of Food and Nutritional Sciences, 2022)
Corrosion is the deterioration of a material by a chemical attack or reaction under the influence of the surrounding environment. Metal corrosion can be due to the attack of Sulphate Reducing Bacteria which causes heavy economic losses to the industries. Sulphate Reducing Bacteria can be inhibited by the growth of Nitrate Reducing Bacteria and that could be a better eco-friendly solution to fight corrosion